REDESAIN INTERIOR KREMATORIUM CENTER MUMBUL DI KABUPATEN BADUNG (Jurnal iSpectrum, 2023)
Based on the regional regulations of the Province of Bali, it is regulated to carry out a simple death procession and is recommended at the crematorium. So that the need for crematorium and funeral services increases in Bali. Especially the Crematorium services in Mumbul. The interior redesign of the Mumbul Crematorium Center with the universal theme and concept of svarga emerged to meet the community's need for a crematorium. The redesigned Mumbul Center Crematorium will have a level of service, comfort, and pay attention to applicable health regulations to support the comfort of the community and fulfill activities. The concept theme is intended to give a new impression on the Mumbul Center Crematorium later. Apart from humans, this design also looks at reducing the impact of air pollution caused by cremated smoke. The Mumbul Center Crematorium with the theme and universal concept of svarga is expected to be able to focus on teaching tolerance to the community and provide deep meaning about life and death to the community.